Synthesis of good quality double-stranded cDNA from the bark tissue of robusta coffee (Coffea canephora) plants - Santosh, P; Sreenath, HL (Research in Biotechnology, 2012)
Quality RNA in large quantity is often required in the analysis of gene expression. RNA extraction from samples collected from woody plants is generally complex and becomes the main limitation to study gene expression particularly in perennial crops like coffee. Standard RNA extraction protocols are time consuming laborious and cannot be adapted for high throughput functional analysis. A simple and effective protocol for extraction of high quality total RNA from bark tissue of woody stem was achieved using the RNeasy plant mini kit (Qiagen, USA). The extracted RNA was successfully converted into double-stranded cDNA using the SMATer cDNA synthesis kit (Clontech, USA) which is based on the Switching Mechanism At 5’ End of RNA Transcript (SMART) technology. The integrity of the total RNA used for synthesizing double stranded cDNA was assessed by amplifying a 1282 bp product targeting the glyceraldehyde 3-phospho dehydrogenase (GAPDH) gene by PCR. As expected, the PCR product contained the full coding sequence plus 69 and 196 bp of 5’ and 3’ UTRs respectively. The double-stranded cDNA was used successfully for creating a SSH cDNA library (results not reported here). The cDNA could also be useful for a number of other applications like cDNA library construction, EST analysis, RACE and Next Generation Sequencing (NGS).